A Novel Luminescent Metal‐Organic Framework as a Remarkable Sensor for Detecting Aristolochic Acids in Biological Fluids. Issue 17 (23rd April 2021) - Song, Lijun; Liu, Meiying; Tian, Fuli; Liu, Zhiliang
Abstract: Abstract : Aristolochic acids (AAs) have caused widespread concern as highly nephrotoxic and carcinogenic substances. Therefore, it is essential to explore a simple and feasible method to detect AAs for disease prevention and clinical diagnosis. In this work, we designed and synthesized a novel luminescent metal organic framework (Zn‐MOF), which has excellent structural stability and fluorescence stability. Notably, the luminescent Zn‐MOF exhibits strong blue emission owing to ligand‐centered electronic transitions, while being capable as a selective sensor for the quantitative detection of AAs in biological fluids with low detection limit. The fluorescence analysis method, possessing the advantages of reliability and high accuracy, further demonstrated that Zn‐MOF has potential applications in monitoring the carcinogen biomarker AAs. Moreover, a paper‐based sensor has been devised by depositing Zn‐MOF on filter paper, which provides a novel strategy for visual, rapid, and on‐site AAs detection with the naked eye. Abstract : A novel luminescent Zn‐MOF with an exceptional performance for detecting aristolochic acids in biological fluids was constructed as a multifunctional sensing platform by hydrothermal synthesis. Meanwhile, the portable paper‐based visual sensor based on Zn‐MOF as a diagnostic tool displays great potential for qualitative and quantitative identification of aristolochic acids.